Teacher community in elementary charter schools. - Cannata, Marisa (Education Policy Analysis Archives, 2007)
The organizational context of charter schools may facilitate the formation of a strong teacher community. In particular, a focused school mission and increased control over teacher hiring may lead to stronger teacher professional communities. This paper uses the 1999-2000 Schools and Staffing Survey to compare the level of teacher community in charter public and traditional public schools. It also estimates the effect of various charter policy variables and domains of school autonomy on teacher community. Charter school teachers report higher levels of teacher community than traditional public school teachers do, although this effect is less than one-tenth of a standard deviation and is dwarfed by the effect of a supportive principal, teacher decision-making influence, and school size. Charter public schools authorized by universities showed lower levels of teacher community than those authorized by local school districts. Teachers in charter schools that have flexibility over tenure requirements and the school budget report higher levels of teacher community. This study reveals that charter schools do facilitate the formation of strong teacher communities, although the effect is small. The analysis also suggests that the institutional origin of the charter school and specific areas of policy flexibility may influence teacher community.